2021
DOI: 10.1007/s10308-021-00617-3
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact of transportation infrastructure investment under the Belt and Road Initiative

Abstract: China launched an ambitious strategy known as the Belt and Road Initiative (BRI) in 2013 with an objective to promote regional economic growth and integration. The initiative was implemented primarily through massive investment in transportation infrastructure development among the Belt and Road countries to improve transportation connectivity and reduce trade costs. While such a strategy has been implemented for more than seven years, it remains unclear to what extent the investment of transportation infrastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Moreover, Zhang et al [19] highlight that investment in roadways, railways, telecommunication, and technology infrastructure helps more road network to be built in OBOR participant countries and enhance transportation of manufactured goods to more markets, hence improving trade. Besides, Chen and Li [20] again prove this positive relationship that infrastructure investment improves productivity, facilitates the formation of new firms, and reduces transportation costs, which combines enhances industrial agglomeration. This then increases the total demand and output expansion of nations along the OBOR trading route, which simultaneously increases the demand factor of GDP, promoting the overall economic growth of these aid receiving nations.…”
Section: Infrastructure Investmentmentioning
confidence: 85%
“…Moreover, Zhang et al [19] highlight that investment in roadways, railways, telecommunication, and technology infrastructure helps more road network to be built in OBOR participant countries and enhance transportation of manufactured goods to more markets, hence improving trade. Besides, Chen and Li [20] again prove this positive relationship that infrastructure investment improves productivity, facilitates the formation of new firms, and reduces transportation costs, which combines enhances industrial agglomeration. This then increases the total demand and output expansion of nations along the OBOR trading route, which simultaneously increases the demand factor of GDP, promoting the overall economic growth of these aid receiving nations.…”
Section: Infrastructure Investmentmentioning
confidence: 85%
“…Lenz, Skender, and Mirković (2018) found that in Central and Eastern Europe (CEE) MS road network development has a significant positive effect on GDP, but railways have a negative effect. Chen and Li (2021) conclude that the economic impact of transport infrastructure investments in the West and Central Europe is relatively minor. Toader, Firtescu, Roman, and Anton (2018) assessed the EU-28 MS ICT infrastructure impact on GDP per capita and found a significant positive effect.…”
Section: Introductionmentioning
confidence: 86%
“…There are a number of methods used by CGE modelers to analyze the economic impacts of commodity trade disruptions. These include the phantom tax, direct commodity output constraints, constraining flow variables through adjustment of tariff variables, productivity shocks, willingness to pay shock and margin shocks (Chen & Li, 2021; Walmsley & Strutt, 2021). We chose the Phantom Tax approach with closure rules that fix capital endowment of the economic disruptions from the War (a type of “medium‐run approach” applicable to simulations that cover only a couple of years).…”
Section: Cge Modelingmentioning
confidence: 99%